Dialysis Adequacy Indices and Body Composition in Male and Female Patients on Peritoneal Dialysis - Debowska, Malgorzata (Multimed Inc, 2014)
♦ Objectives: Creatinine clearance scaled to body surface area (BSA) and urea KT/V normalized to total body water (TBW) are used as indices for peritoneal dialysis (PD) adequacy. We investigated relationships of indices of dialysis adequacy (including KT/V, KT, clearance, dialysate over plasma concentration ratio) and anthropometric and body composition parameters (BSA, TBW, body mass index (BMI), weight, height, fat mass (FM), and fat-free mass (FFM)) in male and female patients on continuous ambulatory peritoneal dialysis. ♦ Methods: Ninety-nine stable patients (56 males) performed four 24-hr collections of drained dialysate for four dialysis schedules with three daily exchanges of glucose 1.36% and one night exchange of either: 1) glucose 1.36%, 2) glucose 2.27%, 3) glucose 3.86% or 4) icodextrin 7.5%. ♦ Results: KT and dialysate over plasma concentration ratio, C(D)/C(P), for urea and creatinine were similar for males and females and, in general, did not depend on body-size parameters including V (= TBW), which means that the overall capacity of the transport system in females and males is similar. However, after normalization of KT to V or 1.73/BSA yielding KT/V and creatinine clearance, Cl((1.73/BSA)), respectively, the normalized indices were substantially higher in females than in males and correlated inversely with body-size parameters, especially in males. ♦ Conclusions: As KT/V depends strongly on body size, treatment target values for KT/V should take body size and therefore also gender into account. As KT is less influenced by body size, body composition and gender, KT should be considered as a potential auxiliary index in PD.